Association Between Abdominal Adipose Tissue Distribution and Obstructive Sleep Apnea in Chinese Obese Patients - Ma, Bingwei; Li, Yingying; Wang, Xingchun; Du, Lei; Wang, Shilin; Ma, Huihui; Zhou, Donglei; Usman, Taofeek; Lu, Liesheng; Qu, Shen (Frontiers in Endocrinology, 2022)
Purpose Factors related to the occurrence of obstructive sleep apnea syndrome (OSAS) in obesity have not been fully clarified. The aim of this study was to identify the association between OSAS and abdominal fat distribution in a cohort of Chinese obese patients. Methods This cross-sectional study collected demographic data of 122 obese patients who were admitted into the in-patient unit of the Department of Endocrinology, Shanghai Tenth People’s Hospital from July 2018 to January 2021. OSAS was diagnosed based on the results of overnight polysomnography, and the abdominal fat distribution was measured by bioelectrical impedance analysis (BIA). Univariate and multivariate logistic regression analyses were used to investigate the association between OSAS and the distribution of abdominal fat. Results (1) The mean age (SD) of the obese patients included was 32.44 (11.81) years old, and the overall incidence rate of OSAS was 51.06%. Twenty-four (25.53%) patients had mild OSAS, 10 (10.64%) had moderate OSAS, and 14 (14.89%) had severe OSAS. The apnea hypopnea index (AHI) of men was significantly higher than that of women (5.50, interquartile range (IQR) 3.80–30.6 vs. 4.2, IQR 1.4–12 events/h, p = 0.014). Meanwhile, men had a significantly higher visceral fat area when compared with women (180.29 ± 51.64 vs. 143.88 ± 53.42 cm2, p = 0.002). (2) Patients with OSAS had a significantly higher waist circumference, fasting plasma glucose, 2 h postprandial plasma glucose, glycated hemoglobin, and visceral fat area than patients without OSAS (all p < 0.05). (3) AHI was significantly positively associated with BMI, neck circumference, waist circumference, and visceral fat area (r = 0.306, p = 0.003; r = 0.380, p < 0.001; r = 0.328, p = 0.002; r = 0.420, p < 0.001) but not with subcutaneous fat area (p = 0.094). Multivariate analysis demonstrated that abdominal fat area and fasting plasma glucose were independent risk factors for OSAS (odds ratio, 1.016; 95% confidence interval, 1.005–1,026, p = 0.005; odds ratio, 1.618; 95% confidence interval, 1.149–2.278, p = 0.006). Conclusions In obese patients, the abdominal visceral adipose deposit but not the subcutaneous fat area was associated with OSAS and was an independent risk factor for OSAS. Therefore, improving the distribution of abdominal fat may contribute to alleviating the severity of OSAS in obesity.